Potential impacts of CO2 leakage on groundwater quality of overlying aquifer at geological carbon sequestration sites: A review and a proposed assessment procedure. Issue 5 (31st August 2021) - Zheng, Liange; Nico, Peter; Spycher, Nicolas; Domen, Jeremy; Credoz, Anthony
Abstract: One of the risks of geologic carbon sequestration (GCS) is the leakage of injected CO2 into overlying groundwater resources, resulting in potential deterioration of the quality of the groundwater due to the increase in acidity, the release of trace metals and organic compounds, and potential changes in microbial activities. A large number of studies have been conducted to evaluate various aspects of the impact of CO2 leakage on overlying aquifers using natural analog, laboratory experiments, field tests, and numerical models. In this paper, we conducted an exhaustive review of the published work, focusing on the statistical assessment of the risk posed by the trace elements including Pb, As, Cd, Ba, and U and identifying the knowledge gaps. Key observations from the review include the following: (1) Pb, As, and U are metals of primary concern because multiple cases showed their concentration higher than maximum contaminant level (MCL) or other regulatory standards, (2) carbonate aquifers seemed more vulnerable to Pb and As contamination but not to U, (3) Cd and Ba are less a concern, only one case showed Cd/Ba concentration higher than MCL, (4) none of the field studies showed the concentrations of Pb and As higher than MCL, although one push–pull field test showed the concentration of U higher than MCL, (5) the order of aggressiveness in terms of releasing trace metals was determined to be as follows: batch experiment > column experiment > field test, and (6) there is no clear correlation between metal release and type of sediments, type of aquifer, the content of carbonate and clay. Evaluation likely has to be done on a case‐by‐case basis. For further operations of CO2 storage overview and screening of potential sites, we suggest the use of an eight‐step environmental risk assessment procedure comprising laboratory experiment, screening modeling work, and field testing for assessing the vulnerability of the overlying aquifers to degradation from CO2 leakage from the GCS site. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd.